Domestikasi Ikan Brilliant Rasbora (Rasbora Einthovenii) Dari Habitat Alami Sebagai Pengembangan Ikan Hias Lokal - Buana, Raditya Cakra; Ramadhani, Ryan Syehan; Wangsa, Nur Robbiah Naffa; Aulya, Augien Devina; Kurniawan, Ardiansyah (Jurnal Perikanan dan Kelautan, 2025)
The Brilliant Rasbora (Rasbora einthovenii) is a local freshwater species from the Bangka Belitung Islands with high potential as an ornamental fish. However, its current utilization still depends on capture from natural habitats. This study aimed to determine the initial domestication stages of R. einthovenii to assess its adaptation to controlled environments and acceptance of artificial feed. The experiment was conducted over 26 days using 30 fish reared in plastic tanks and ad satiation fed using commercial feed. Results showed that the fish began accepting artificial feed on day 4. The SGR, FCR, and SR values were 0.38%, 5.20, and 60%, respectively. Water quality parameters remained within optimal ranges, but improvements in feeding and culture management are necessary to enhance growth and survival rates.